Evaluation of thermomechanical aging intervals associated with mechanical degradation of CAD/CAM materials in a chewing simulator - Xiaojie Wang; Luiza Freitas Brum Souza; Moody Kaldas; Enkelejd Angelo Cankja; Tan Fırat Eyüboğlu; Mutlu Özcan (BMC Oral Health, 2026)
Abstract Purpose To evaluate the influence of different thermomechanical aging intervals on the flexural strength and reliability of CAD/CAM restorative materials and to identify aging conditions that induce measurable mechanical degradation. Methods Specimens ( N = 192) (16 × 4 × 2 mm 3 ) were made from four CAD/CAM materials: resin-based composite (Brilliant Crios), lithium silicate ceramic (Initial LiSi Block), lithium disilicate ceramic (IPS e.max CAD), and monolithic zirconia (IPS e.max ZirCAD MT). Samples followed ISO 6872 (2015) for flexural strength testing and were divided into four aging groups ( n = 12): baseline, 100,000, 600,000, and 1,200,000 cycles. Flexural strength was measured with a three-point bend test (1 mm/min, 12 mm span). Data were analyzed using ANOVA and Tukey’s test (α = 0.05), and reliability was evaluated via Weibull analysis. Results Thermomechanical aging significantly reduced LD’s flexural strength ( p = 0.022), but not significantly for Composite ( p = 0.141), LiSi ( p = 0.158), or Zirconia ( p = 0.064). The flexural strength of LD decreased by 23.1% after 600,000 cycles, while all materials showed their largest reduction then, but no significant differences were found among them. Weibull analysis showed a significant reliability drop in LD, with the lowest Weibull modulus after 600,000 cycles, while the reliability of others remained the same. Conclusions Lithium disilicate was the only material significantly impacted by aging, with the 600,000-cycle group showing the greatest observed reductions in flexural strength and reliability among the evaluated intervals. In contrast, Composite, LiSi, and Zirconia were not significantly affected, indicating greater resistance to thermomechanical fatigue.